Asymmetric Distribution of pl10 and bruno2, New Members of a Conserved Core of Early Germline Determinants in Cephalochordates - Dailey, Simon C.; Febrero Planas, Roser; Rossell Espier, Ariadna; Garcia-Fernàndez, Jordi; Somorjai, Ildikó M. L. (Frontiers in Ecology and Evolution, 2016)
Molecular fingerprinting of conserved germline and somatic ¨stemness¨ markers in different taxa have been key in defining the mechanism of germline specification ("preformation" or "epigenesis"), as well as expression domains of somatic progenitors. The distribution of molecular markers for primordial germ cells (PGCs), including vasa, nanos and piwil1, as well as Vasa antibody staining, support a determinative mechanism of germline specification in the cephalochordate Branchiostoma lanceolatum, similarly to other amphioxus species. pl10 and bruno2, but not bruno4/6, are also expressed in a pattern consistent with these other germline genes, adding to our repertoire of PGC markers in lancelets. Expression of nanos, vasa and the remaining markers (musashi, pufA, pufB, pumilio and piwil2) may define populations of putative somatic progenitors in the tailbud, the amphioxus posterior growth zone, or zones of proliferative activity. Finally, we also identify a novel expression domain for musashi, a classic neural stem cell marker, during notochord development in amphioxus. These results are discussed in the context of germline determination in other taxa, stem cell regulation and regenerative capacity in adult amphioxus.